2011
DOI: 10.3109/10428194.2011.593273
|View full text |Cite
|
Sign up to set email alerts
|

Can fluorodeoxyglucose positron emission tomography/computed tomography avoid negative iliac crest biopsies in evaluation of marrow involvement by lymphoma at time of initial staging?

Abstract: The assessment of bone marrow involvement (BMI) is important for accurate prognostication and deciding the appropriate therapy in patients with lymphoma. Conventional bilateral iliac crest biopsies (ILBMBs) have many limitations. F-18 fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) is a useful investigative tool for detecting BMI. F-18 FDG PET/CT data for 97 patients with either non-Hodgkin lymphoma (NHL) or Hodgkin lymphoma (HL) were analyzed. ILBMB was performed 7-10 days lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
3
23
1
3
Order By: Relevance
“…This proposal is distinct from those of Khan et al [14], and Berthet et al [15], in that, in PET/CT negative cases, the former precludes BMB, while the latter considers it an option; therefore, according to our data, 10% of patients will be understaged with those approaches. In addition, it is distinct from those proposed by Mittal et al and Kostakoglu et al, in that they advise BMB in positive PET/CT, which is clinically unnecessary according to our data [24,25].…”
Section: Discussioncontrasting
confidence: 84%
“…This proposal is distinct from those of Khan et al [14], and Berthet et al [15], in that, in PET/CT negative cases, the former precludes BMB, while the latter considers it an option; therefore, according to our data, 10% of patients will be understaged with those approaches. In addition, it is distinct from those proposed by Mittal et al and Kostakoglu et al, in that they advise BMB in positive PET/CT, which is clinically unnecessary according to our data [24,25].…”
Section: Discussioncontrasting
confidence: 84%
“…Moreover, bone marrow status according to 18 F-FDG PET/CT appears to be a better independent prognostic factor than bone marrow status according to BMB. Several studies have already described the capacity of 18 F-FDG PET/CT to detect BMI in patients with DLBCL (12)(13)(14)(15)(16)(17)(18)(19)23). In our homogeneous series of patients, BMI was assessed in 25% of patients according to our criteria.…”
Section: Discussionmentioning
confidence: 97%
“…18 F-FDG PET/ CT findings were considered positive for BMI in cases of uni-or multifocal bone marrow 18 F-FDG uptake that could not be explained by benign findings on the underlying CT image or history (e.g., fractures) (19,23). In contrast, diffuse intense bone marrow 18 F-FDG uptake was considered negative for BMI; indeed, it has been demonstrated that diffuse intense uptake is significantly related to anemia or inflammatory processes ( Fig.…”
Section: F-fdg Pet/ct Analysis and Bmimentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there was a significant difference in the capability of PET/CT to detect BM infiltration according to histological type of NHL. It has been reported in the literature that the performance of PET/ CT in evaluating the BM infiltration in indolent lymphomas was poor [18,21]. Since, indolent lymphomas comprise a number of different lymphoma types, we did not perform a subgroup analysis in this heterogeneous group.…”
Section: Discussionmentioning
confidence: 99%